Mitochondrial tRNA mutations in Chinese hypertensive individuals - Liu, Yuqi; Li, Yang; Wang, Xin; Ma, Qinha; Zhu, Chao; Li, Zongbin; Yin, Tong; Yang, Jie; Chen, Yundai; Guan, Minxin (Mitochondrion, 2016)
Hypertension is a very important risk factor for cardiac vascular disease. The previous studies showed that mitochondrial DNA mutations are associated with cardiovascular disease, including hypertension. In this study we did systematical analysis on the total 22 mitochondrial tRNAs and the clinical, genetic and molecular changes of 140 Chinese hypertension and 124 controls. This analysis identified 22 nucleotide changes among 15 different tRNA genes. There are 15 mutations with CI (Conservation index) larger than 75%. Of these, there are 26 patients with CI larger than 75% in the HTN group, higher than the 6 subjects in the control group (P=0.00). The tRNA(Phe) G586A, tRNA(Lys) G8313A and tRNA(His) G12147A mutations create highly conservative base-pairings on the D-stem, tRNA(Lys) G8342A on the T-stem, tRNA(Phe) T616C, tRNA(Ala) T5628C, tRNA(Tyr) G5856A and tRNA(Thr) A15924G on the AC stem, tRNA(Leu(CUN)) G12300A on the AC loop, tRNA(Met) C4467T, tRNA(Trp) T5578C, tRNA(Lys) A8296G, tRNA(Arg) T10463C and tRNA(Thr) C15891T on ACC stem, and tRNA(Ser(UCN)) C7492T on D-A junction, while the other tRNA variants were polymorphisms. The pedigrees of PLAH78 carrying the T5578C, PLAH84 carrying the C4467T, PLAH60 carrying the T5628C and PLAH118 carrying the C7492T mutation exhibited maternal transmission of essential hypertension. Sequence analysis of their mitochondrial genomes revealed the presence of T5578C, C4467T, T5628C or C7492T mutations but the absence of other functionally significant mutations in all matrilineal relatives of these families. These tRNAs mutations, associated with altered structures of tRNAs and mitochondrial dysfunction, may contribute to the hypertension in Chinese population. A lot of work still should be done for the mechanism and functional effect of the mtDNA mutation on hypertension.